Axillary Glomus Tumor Revealed by FDG PET/CT. (20th October 2021) - Shen, Guohua; Wang, Rang; Pan, Lili; Kuang, Anren
Abstract: Glomus tumors are vascular neoplasms arising from glomus bodies. They are typically found in tissues where glomus bodies are concentrated, including the subungual layer of the fingers or the deep dermis of the palm, wrist, forearm, and foot but rarely occur in the axillary region. Herein, we reported the MRI and FDG PET/CT findings of a glomus tumor presenting as an axillary mass in a 25-year-old woman.